Effects of microbial inoculation on composting of household organic waste using passive aeration bin - Somjai Karnchanawong; Siriwan Nissaikla (International Journal of Recycling of Organic Waste in Agriculture)
Background The effects of microbial inoculation with two commercial inoculants and mature compost on the composting of household organic wastes were investigated using five 200-L passive aeration compost bins. Food scraps and dry leaves (1.6 kg total) with a ratio of 1:0.14 (wet weight) were added to each bin once a day, for 60 days, and then further composted for an additional 94 days. The temperature in each bin was recorded daily. Weekly to biweekly, a composite sample of the compost from each bin was analyzed. Results The C/N ratios of composts in the un-seeded and seeded bins stabilized at 81 days and 67â74 days, respectively. The highest volatile solid mass reduction was achieved in the bin seeded with 5 % mature compost. Conclusions The study revealed that it might not be necessary to add commercial inoculants to facilitate composting of household organic waste. Mature compost can be used as a seed starter to improve composting.